Genre Pedagogy to the Teaching of Academic Writing in Tertiary Level and Cognitive Empowerment - Murti Ayu Wijayanti; Emi Emilia; Wawan Gunawan (English Department - University of Sultan Ageng Tirtayasa, 2017)
This paper reports a small part of the study which focuses on the use of genre pedagogy to the teaching of writing research proposal as one of academic texts in tertiary level. This study aims at finding out how genre pedagogy can empower students cognitively through their abilities in writing research proposal. A case study involving fifteen students in one university in Banten taking Research on ELT subject was conducted using classroom observation and related documents, such as researcher‟s field notes and students‟ journal. The classroom observation and related documents analysis result showed that the students were cognitively empowered through the teaching cycles of genre pedagogy through various activities which encouraged their cognitive processes. Thus, genre pedagogy can empower students cognitively through its various learning activities and texts examples.Keywords: academic writing; cognitive empowerment; genre pedagogy